Agency labor as a non-standard employment development factor (Journal of Economic Research & Business Administration, 2018)
Globalization and the post-industrial era require entities to use new methods to reduce productioncosts. At this stage of development, outsourcing is becoming more and more popular for the workforcedispatching. The advantage of agency work lies in its flexibility. Against the backdrop of the agency workpositive aspects, there are difficulties for both employers and workers causing disagreements arising fromineffective relations between market participants due to enforcement (mainly in countries with transitioneconomies) and poor labor relations regulation. These circumstances cause a conflict of interest illustratingsocial injustice. The purpose of the article is to study the peculiarities of outsourcing in the laborlegislation sphere on the developed countries example. To study the legal framework of agency workin Kazakhstan. Identify the problems of the emergence of outsourcing as a type of agency work. Thisarticle presents foreign experience in the development of agency labor in Germany, the United Statesof America, Great Britain and Japan, where a comparative approach has been applied to the study ofagency work in developed countries. The issues of agency work formation and regulation are coveredin these countries.The issues of agency work formation in Kazakhstan, in particular, employment agencies, were alsostudied. The civil law base serves as a foundation for studying agency work, outsourcing in particular.For the convenience of studying the agency work, a comparative approach is used in the agency worksphere, which reflects positive and negative aspects of outsourcing as a kind of agency work. The importanceof the article is to systematize the agency work formation issues in Kazakhstan in the legal sphere,where indirect methods of regulation are reflected. The experience of reforming shows that in developedcountries, the government should establish more flexible outsourcing rules that can ensure fairness for allplayers in the agency work market.